Characterization of antigen-binding protein in earthworms Lumbricus terrestris and Eisenia foetida - Tucková, L; Rejnek, J; Bilej, M; Pospísil, R (Developmental and comparative immunology, 1991)
Injection of antigen into the annelid worms Lumbricus terrestris (LT) and Eisenia foetida (EF) results in a marked increase of coelomic fluid protein concentration and the formation of a protein which binds the stimulating antigen (3). In this report we show that the increases in total protein concentration after first and second doses of antigen were higher and were achieved earlier in LT than in EF, while the accumulation of antigen-binding protein in coelomic fluid was similar in both species. Antigen-binding protein isolated by affinity chromatography retained its original binding activity. Its molecular weight in coelomic fluid as well as after isolation was 56 kD when analyzed by SDS-PAGE and immunoblotting. Under reducing conditions, two bands with mol./wt. 31 and 33 kD appeared which did not reveal detectable binding activity. This suggests that the 56 kD binding protein of annelids is composed of two disulphide-linked polypeptide chains both of which participate in antigen-binding site formation.
Keywords: Molecular Weight; Antigens; imunoglobulin G; antigeny; molekulová hmotnost; proteiny; sérový albumin; Body Fluids; kyselina arsanilová; skot; tělesné tekutiny; Serum Albumin; chromatografie afinitní; Immunoglobulin G; Oligochaeta; Arsanilic Acid; zvířata; Humans; Cattle; Species Specificity; druhová specificita; Chromatography, Affinity; Proteins; lidé; Animals